Ensaios em economia da educação - Cavalcanti, Gabriella da Silva (2020)
This dissertation is composed of three independent essays in economics of education that have as general objective to contribute to the national literature of economics of education through the estimation of microechonometric models. The first essay aims to analyze the incidence and the effects of overeducation on the incomes of workers graduated from the state of São Paulo, in the period 2003-2013, in order to control for unobserved individual heterogeneity, as well as to measure the duration of the phenomenon and its determinants. To achieve this objective, the measurement of the required schooling was obtained through the Job Analysis method based on the information of CBO 2002. Were considerated the 148 occupational families of CBO 2002 that require higher education and used the microdata of the RAIS-Migra. The results revealed an over-education rate of about 27% in the State of São Paulo with a tendency to decline in the period. By estimating the Verdugo and Verdugo (1989) income equation, the results pointed out that the fixed effect model is the most appropriate, revealed negative over-education returns substantially reduced when compared to cross-section estimates, confirming the initial hypothesis of a study that the high returns of over-education found in the literature are resulting from omitted variable bias. The analysis of overeducation duration through survival analysis technique showed a drop in the likelihood of continuing over-educated over time and that individual, employment, spatial and macroeconomic characteristics determine the individual’s departure from the over-educated condition. The second essay aims evaluate the impact of the bonus payment program to teachers of the Government of Paraíba State on the average proficiency in portuguese and mathematics, the school approval rate and abandonment rate of the students from 5º/9º years award-winning schools. Due to the unavailability of data and the inconstancy of the program selection criteria during its validity, were used the methods of PSM and Differences in Differences to evaluate the impact of the program in a specific year, 2016. To this end, the microdata of the SAEB and the School Census for the years 2015 and 2017 were used for public schools in the State of Paraíba, available through the INEP. The results of the estimates revealed the lack of impact of the bonus programme on the result indicators of the award-winning schools, suggesting an inefficiency of the bonus in conditioning better school performance. The third essay investigates the overflow of the quality of education among municipalities through average proficiency in Portuguese and mathematics for students of the final years of elementary school by of econometric spatial models. Were are used microdata of SAEB and data from the Child and Adolescent Observatory, of the IBGE and of the FINBRA Portal, the period of analysis is the years 2011 and 2015 for the 5570 Brazilian municipalities. The results obtained confirmed the initial hypothesis of the study of the existence of educational spillovers among the municipalities, being found evidences of spatial dependence in the school performance of the municipalities and in the explanatory variables, suggesting that the best specification is given by the SDM.